2010
DOI: 10.1590/s0080-62342010000200029
|View full text |Cite
|
Sign up to set email alerts
|

Efeito da música no trabalho de parto e no recém-nascido

Abstract: Music has been applied for balancing energies that have been disturbed by the stress of modern life. The objective of the present study was to verify the effect of music in labor and on the newborn, when submitted to the same melodies heard by their own mothers during pregnancy. Pregnant women, Health Center users, were submitted to musical sensitization sessions since their fifth month of pregnancy. During labor, the melodies previously selected by the pregnant women were played all the time with a thirty-min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
23

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 3 publications
(6 reference statements)
1
20
0
23
Order By: Relevance
“…Some of these studies were not randomized, the sample size in the music group was small, and pain measures were not reported [14,15,16,17]. There were only two randomized controlled trials in the literature that investigated the effect of music on labor pain with a music and control group [2,12].…”
Section: Discussionmentioning
confidence: 99%
“…Some of these studies were not randomized, the sample size in the music group was small, and pain measures were not reported [14,15,16,17]. There were only two randomized controlled trials in the literature that investigated the effect of music on labor pain with a music and control group [2,12].…”
Section: Discussionmentioning
confidence: 99%
“…Kafali et al showed that mothers’ listening to music increased movement of the fetus and its heartbeat rate(27). Tabarro also found that the women who listened to music in their delivery room suffered less pain and stress and had a better delivery experience (28). Attending religious and spiritual ceremonies also managed pregnancy complications via decreasing stress and worry and establishing self-confidence (29).…”
Section: Discussionmentioning
confidence: 99%
“…Por intermédio de convite verbal, foram abordadas participantes que estavam no período pré-parto e internadas no Centro Obstétrico, e, destas, foram recrutadas aquelas que atendiam aos critérios de inclusão e exclusão, compondo assim a amostra do presente estudo. Foi possível verificar que as informações obtidas não apresentavam dados novos por meio do critério de saturação dos dados 4 . Os discursos obtidos nas entrevistas foram registrados e gravados através de um aplicativo de voz da Samsung-Galaxy Ace GTS5830B®, sendo transcritos na íntegra e analisados segundo a modalidade temática proposta por Minayo 5 , determinando-se as Unidades de Significados dos relatos e a categorização dos dados.…”
Section: Métodounclassified
“…Dentre as práticas para a humanização do pré-parto, há a aplicação da música, que tem sido um elemento capaz de aliviar as dores durante as contrações, auxiliar na diminuição da tensão e do medo, na ambientalização da parturiente no hospital, além de promover um estímulo pela busca pela espiritualidade, sendo um diferencial para a paciente 4 .…”
Section: Introductionunclassified